Effects of group-based versus individual physical exercise programs for knee osteoarthritis: A systematic review and meta-analysis: Exercises modalities for knee osteoarthritis - R. de Jesus Júnior, Everaldo; de L. Lopes, Clécio; Gomes Neto, Mansueto; de F. Dantas, Glauko André; Mendes Maranhão, Diógenes C.; D. de A. Angelo, Fernando; Trombini-Souza, Francis; A. da Silva, Tarcísio F. (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Knee osteoarthritis (OA) is the most common joint disease worldwide and is associated with a high rate of disability and poor quality of life. However, little is known about the therapeutic effects of group-based versus individual-based physical exercise protocols. Objective: To investigate the effects of individual versus group-based physical exercises on pain intensity and functional outcomes in people with knee OA. Methods: MEDLINE/PubMed, Cochrane, EMBASE, and PEDro databases were searched from the earliest date available to July 2023. Study quality was evaluated using the PEDro scale. Mean difference (MD), standardized mean difference (SMD), and 95% confidence interval (CI) were calculated using a random effect model. Results: Six studies, with 763 patients, met the study criteria. Group-based physical exercises improved pain intensity (VAS 0-100) MD -17.2 (95% CI: -22.2 to -12.3), the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale MD -0.54 (95% CI: -1.0 to -0.08), WOMAC function subscale MD -2.1 (95% CI: -4.1 to -0.08) compared to individual modality. No significant difference regarding muscle strength and exercise tolerance was found for participants in the group-based physical exercises compared with individual physical ones. Conclusion: Group-based physical exercise was more successful in reducing pain intensity and functional impairment in patients with knee OA than individual exercise programs. Both group-based and individual physical exercise programs enhanced muscle strength and 6-minute walk distance.